Effect of Granulocyte-colony stimulating factor with or without Moxifloxcacin therapy on capsulated Staphylococcus aureus infection in neutropenic mice (Baghdad Science Journal, 2025)
Twenty bacterial isolates were identified as Staphylococcus aureus collected from wounds and catheters related infections. A capsulated S. aureus isolate was chosen after performing serum soft agar test, for this study Neutropenic mice were challenged with capsulated S. aureus ,and the effect of G-CSF with or without moxifloxacin was studied.The results indicated that the addition of G-CSF to moxifloxacin therapy have a synergistic effect in the killing of the bacteria, while when each G-CSF and moxifloxacin were used seperately have a similar effect on bacterial killing. It was found that the moxifloxacin has the same activity as G_CSF but is less costly than the latter one.